First enantiospecific synthesis of (-)-parvifoline and (-)-curcuquinone - Chavan, Subhash P.; Thakkar, Mahesh; Jogdand, Ganesh F.; Kalkote, Uttam R. (Journal of Organic Chemistry, 2006)
The first enantiospecific synthesis of (-)-parvifoline, employing ring-closing metathesis as the key step, and (-)-curcuquinone from naturally occurring (R)-(+)-citronellal is described.

Enantioselective synthesis of (R)-(+)-alpha-lipoic acid via proline-catalyzed sequential alpha-aminoxylation and HWE olefination of aldehyde - Panchgalle, Sharad P.; Jogdand, Ganesh F.; Chavan, Subhash P.; Kalkote, Uttam R. (Tetrahedron Letters, 2010)
An efficient enantioselective synthesis of (R)-(+)-alpha-lipoic acid is described, in high optical purity (>97% ee), using L-proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde as the key step. (C) 2010 Elsevier Ltd. All rights reserved.

Synthesis and structural characterization of homochiral homo-oligomers of parent CIS- and trans-furanoid-beta-amino acids - Pandey, Sunil K.; Jogdand, Ganesh F.; Oliveira, Joao C. A.; Mata, Ricardo A.; Rajamohanan, Pattuparambil R.; Ramana, Chepuri V. (Chemistry-A European Journal, 2011)
The synthesis of homochiral homo-oligomers of cis- and trans-3-aminotetrahydrofuran-2-carboxylic acids (parent cis- and trans-furanoid-beta-amino acids, referred to as ``cis-/trans-FAA'') has been carried out to understand their secondary structures and their dependence on the ring heteroatom. The oligomers of two diastereomers have been shown to have a distinct left-handed helicity. The cis-FAA homo-oligomers show a 14-helix structure, in contrast to the homo-oligomers of cis-ACPC, which adopt a sheet like structure. The trans-FAA homo-oligomers were found to adopt a 12-helix structure, the same trend found in trans-ACPC homo-oligomers. With the help of ab initio calculations, the structural features of cis-ACPC and cis-FAA hexamers were compared. We believe that the more compact packing of the cis-FAA hexapeptide should be due to a more favorable interaction between the ring and the backbone amide hydrogen.
Keywords: ab initio calculations; Amino acids; Density functional calculations; Peptides; secondary structures

Synthesis and structural characterization of homochiral homo-oligomers of cis-gamma-methoxy-substituted cis- and trans-furanoid-beta-amino acids - Giri, Awadut G.; Jogdand, Ganesh F.; Rajamohanan, Pattuparampil R.; Pandey, Sunil K.; Ramana, Chepuri V. (European Journal of Organic Chemistry, 2012)
Herein we describe the synthesis of cis-/trans-3-aminotetrahydrofuran-2-carboxylic acids (cis-/trans-FAA) having a ?-methoxy group cis to the amine. The homo-oligomers of these two diastereomeric FAAs have been prepared. Preliminary investigation of their solution secondary structures revealed that they are the same as the homo-oligomers of the parent cis-/trans-FAA with the methoxy group only being a spectator substituent.
Keywords: Amino acids; helical structures; Oxygen heterocycles; Peptides

Stereoselective approach to indolizidine and pyrrolizidine alkaloids: total synthesis of (-)-lentiginosine, (-)-epi-lentiginosine and (-)-dihydroxypyrrolizidine - Kauloorkar, Shruti Vandana; Jha, Vishwajeet; Jogdand, Ganesh F.; Kumar, Pradeep (Organic & Biomolecular Chemistry, 2014)
A simple and highly efficient approach to hydroxylated pyrrolizidine and indolizidine is developed from an aldehyde as a starting material using organocatalytic and asymmetric dihydroxylation reactions as key steps. Its application to the total synthesis of (-)-lentiginosine, (-)-epi-1,2-lentiginosine and (-)-dihydroxypyrrolizidine is also reported.

Stereocontrolled synthesis of Hagen's gland lactones via iterative proline catalyzed alpha-aminoxylation and oxa-Michael addition reactions - Kauloorkar, Shruti Vandana; Jha, Vishwajeet; Jogdand, Ganesh F.; Kumar, Pradeep (RSC Advances, 2015)
A simple and efficient synthesis of Hagen's gland lactones was achieved using a sequential alpha-aminoxylation/oxa-Michael approach in a highly diastereoselective manner with assignment of relative configurations. This method was found to be applicable to the synthesis of various other isomers of Hagen's gland lactones.